Evaluation of The Application of Mental Spiritual Guidance at The Youth Social Services Center (PPS) of The West Nusa Tenggara - Hidayat, Wahyu; Zubair, Maimun; Winengan; Lubna (Alif Lam : Journal of Islamic Studies and Humanities, 2025)
This research wants to explore more deeply the benefits of guidance that integrates religious and spiritual dimensions in supporting the social recovery of teenagers. This research uses a program evaluation design with a qualitative approach with the research subjects being PPS caregivers and adolescent beneficiaries who were selected using a purposive sampling technique. The data collection techniques used in this research were in-depth interviews, observation and documentation to obtain comprehensive and high-quality data. The research results show that the mental spiritual guidance program at the West Nusa Tenggara, PPS has had a major impact on improving the psychological well-being of teenagers. The success of this mental spiritual guidance program is influenced by several factors such as the policy for implementing mental spiritual guidance and the psychological condition of the young beneficiaries before taking the guidance.